Synthesis of hydroxyapatite nanoparticles and its effect on Raphanus sativus seedlings - Flores-Hernández, Eduardo Arón; Lira Saldivar, Ricardo Hugo; Ruiz Torres, Norma Angélica; García López, Josué Israel; Moreno Reséndez, Alejandro; Rodríguez Dimas, Norma; Preciado Rangel, Pablo; Mendoza-Retana, Saraí Shesareli (Ecosistemas y Recursos Agropecuarios, 2021)
The potential of nanofertilizers to increase crop yields has recentlybeen reported. Hydroxyapatite nanoparticles (nHAp) are applied asfertilizers to plants due to their high content of P and Ca (Ca10(PO4)6(OH)2),but there is little information in this regard. The objective of the work was toproduce synthetic nHAp, characterize it and evaluate its effect as a nutrient inthe development of seedlings of radish (Raphanus sativus) variety Champion.The synthesis of nHAp was carried out using an aqueous solution of calciumhydroxide [Ca(OH)2] and orthophosphoric acid (H3PO4). To analyze its biologicaleffect, a bioassay was established with seven treatments on radish seeds with thefollowing concentrations: control (distilled water, T1); 25 (T2); 50 (T3); 100 (T4);200 (T5); 500 (T6) and 1000 mg L-1 (T7); the seedlings developed up to sevendays after sowing. The results show that a concentration of 1 000 mg L-1 reducedgermination by 14.4% compared to the control treatment (0 mL-1). While the vigorof the seedlings was reduced 11.2% with 500 mg L-1. The plumule and radicledid not show significant differences by the treatments with respect to the control,however, a statistical difference was observed with the doses of 25 and 200 mgL-1, when inhibiting and promoting the growth of the seedlings, respectively. Highconcentrations of nHAp were found to have adverse effects on seeds. Finally, then HAp stimulated biomass production.